2008
DOI: 10.1002/eqe.871
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical studies on the response of freestanding laboratory equipment to earthquake shaking

Abstract: SUMMARYThis paper presents results of a comprehensive experimental program on the seismic response of fullscale freestanding laboratory equipment. First, quasi-static experiments are conducted to examine the mechanical behavior of the contact interface between the laboratory equipment and floors. Based on the experimental results, the response analysis that follows adopts two idealized contact friction models: the elastoplastic model and the classical Coulomb friction model. Subsequently, the paper presents sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
141
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 20 publications
1
141
0
1
Order By: Relevance
“…The shake table experiments presented in Konstantinidis and Makris (2009) indicated that the primary mode of response is sliding. However, rocking and possible overturning may happen for interfaces with larger coefficients of friction, μ, and for equipment with more slender configurations (smaller α).…”
Section: Validation Of the Working Model Softwarementioning
confidence: 99%
See 3 more Smart Citations
“…The shake table experiments presented in Konstantinidis and Makris (2009) indicated that the primary mode of response is sliding. However, rocking and possible overturning may happen for interfaces with larger coefficients of friction, μ, and for equipment with more slender configurations (smaller α).…”
Section: Validation Of the Working Model Softwarementioning
confidence: 99%
“…In practice, excessive sliding is prevented by restraining the equipment. Although this may succeed in reducing sliding displacements, it substantially amplifies accelerations (Konstantinidis and Makris 2005b). The problem of equipment sliding has been studied in the past at various scales by Shao and Tung (1999), Lopez Garcia and Soong (2003a,b), and Hutchinson and Chaudhuri (2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a simple freestanding rocking block has been systematically studied for more than five decades both when the block is assumed rigid [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and when it assumed deformable [27][28][29][30][31][32][33][34][35][36][37]. Small scale experiments have been also performed [38][39][40][41][42][43][44][45][46][47][48][49][50][51]. It has been proven that structures that rock inplane (2d rocking) have remarkable dynamic stability.…”
Section: Introductionmentioning
confidence: 99%